Kinship and a counter‐hegemonic social order: former revolutionaries in southern Oman - Wilson, Alice (Journal of the Royal Anthropological Institute, 2020)
Les réinterprétations critiques des travaux en anthropologie de la parenté ont remis en question les idées antérieures selon lesquelles les relations de parenté reflètent et reproduisent un ordre social dominant. Pourtant, les études consacrées aux nouvelles formes de parenté tendent à montrer que celles‐ci peuvent reproduire des idées traditionnelles concernant la famille, les valeurs et les hiérarchies sociales. Pour résister aux tendances actuelles liant la parenté à une reproduction sociale conservatrice, une piste prometteuse est la meilleure compréhension des circonstances dans lesquelles les relations de parenté reproduisent un ordre social anti‐hégémonique. Parmi les anciens militants du mouvement de libération révolutionnaire, aujourd'hui vaincu, de Dufar, dans le sultanat d'Oman, les pratiques de parenté visualisent des réseaux et relations entre anciens combattants qui transgressent les hiérarchies tribales, ethniques, raciales et genrées dominantes. Ces pratiques montrent comment, même dans les circonstances peu propices de la défaite politique et de la marginalisation, les relations de parenté peuvent reproduire un ordre social anti‐hégémonique, tout en offrant une rémanence sociale à la révolution vaincue.
Keywords: Dhofar

Afterlives of Revolution: Everyday Counterhistories in Southern Oman - Wilson, Alice (Stanford University Press, 2023)
The Dhufar Revolution was fought between 1965–1976, in an attempt to depose Oman's British-backed Sultan and advance social ideals of egalitarianism and gender equality. Dhufar, the southernmost governorate in today's Sultanate, captured global attention for its revolutionaries and their liberation movement's Marxist-inspired social change. But following counterinsurgency victory, Oman's government expunged the revolution from sanctioned historical narratives. Afterlives of Revolution offers a groundbreaking study of the legacies of officially silenced revolutionaries. How do their underlying convictions survive and inspire platforms for progressive politics in the wake of disappointment, defeat, and repression?Alice Wilson considers the "social afterlives" of revolutionary values and networks. Veteran militants have used kinship and daily socializing to reproduce networks of social egalitarianism and commemorate the revolution in unofficial ways. These afterlives revise conventional wartime and postwar histories. They highlight lasting engagement with revolutionary values, the agency of former militants in postwar modernization, and the limitations of government patronage for eliciting conformity. Recognizing that those typically depicted as coopted can still reproduce counterhegemonic values, this book considers a condition all too common across Southwest Asia and North Africa: the experience of defeated revolutionaries living under the authoritarian state they once contested.
Keywords: Dhofar

Alice Wilson, Afterlives of Revolution. Everyday Counterhistories in Southern Oman - Boulay, Sébastien (L’Homme. Revue française d’anthropologie, 2024)
Ce n’est pas la première fois qu’Alice Wilson nous invite à découvrir un mouvement révolutionnaire du monde arabo-musulman et ses réminiscences dans le présent. Notre collègue de l’Université de Sussex au Royaume-Uni s’était en effet déjà fait connaître en 2016 par un ouvrage consacré au mouvement de libération du Sahara occidental, le Front Polisario, et à la République arabe sahraouie démocratique, dans lequel elle se penchait sur la question de la souveraineté exercée par cet État exilé de...
Keywords: Recension

Afterlives of revolution: everyday counterhistories in southern Oman: by Alice Wilson, Stanford, CA, Stanford University Press, 2023, 336 pp., ISBN 978-1-5036-3578-4. - Alsraiha, Kassim (British Journal of Middle Eastern Studies, 2025)
Keywords: Recension

Afterlives of Revolution: Everyday Counterhistories in Southern Oman Alice Wilson (Stanford, CA: Stanford University Press, 2023). Pp. 336. $30.00 paper. ISBN: 9781503635784 - Lori, Noora (International Journal of Middle East Studies, 2025)
Keywords: Recension